Implementasi Metode Adaptive Neuro Fuzzy Inference System (ANFIS) dalam Prediksi Harga Saham X - Damayanti, Adelia; Agustina, Dwi (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
Today, the stock market is one of the most important financial vehicles. Investors were concerned about X shares because it fluctuated significantly during Elon Musk's acquisition process. This study was aimed to predict the future price trend of X stocks. Thus, this analysis can assist investors in controlling X stocks. Data for this study were gathered from the Kaggle website. This study uses data from January 2016 to October 2022. The Adaptive Neuro Fuzzy Inference System (ANFIS) will be used to estimate the price of X stocks. The results demonstrated that the ANFIS approach accurately captured the pattern of stock price changes. Based on the accuracy test results, this method has an RMSE of 0.005. It demonstrates that the ANFIS method can accurately anticipate the price of X stock.